The Ordazy cities. The first archaeological research works in the cities of Sortobe 1, 2 - Yeleuov, Madiyar; Tazhekeev, Azilkhan; Moldakhmet, Arkhad; Zhusupnazar, Magzhan (Turkic Studies Journal, 2024)
The article presents written data on the sites, located in the lower reaches of the Syr Darya river and extensive information about the archaeological research conducted in the Sortobe group of cities. It examines the main written sources, works of Arab-Persian researchers of the 9th-12th centuries, including rare information related to sites of the Oghuz period in the lower reaches of the Syr Darya river, which is presented for the first time. In addition, detailed information concerning events in the lower reaches of the Syr Darya, mentioned in the works of Western researchers in the last quarter of the 19th century is considered, memories of some local historians of the Tsarist Russia times and archival data of the Khorezm archaeological-ethnographic expedition are аnalyzed. The article highlights the process of studying the site and the archaeological excavations conducted there with results. This paper discusses the current state of the medieval city of Sortobe. It highlights that half of the city has been eroded by the Syr Darya river, leading to the cultural layer of the site being in an emergency condition without state protection.